Optical laminate

By using a siloxane compound on the peeling surface of the peeling film and satisfying the specific XPS spectrum intensity ratio relationship, the problems of difficulty in removing the peeling film and breaking the adhesive layer in the prior art are solved, and uniform peeling of the adhesive layer and stability of the laminated body are achieved.

CN119731568APending Publication Date: 2025-03-28SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063305.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-08-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the peeling force between one release film and the adhesive layer is relatively small in the adhesive sheet, while the peeling force between the other release film and the adhesive layer is relatively large, which makes it difficult to remove the peeling film in the laminated body and easily leads to breaking of the adhesive layer.

Method used

By including a siloxane compound on the peeling surface of the peeling film and satisfying a specific XPS spectrum intensity ratio relationship (Ys/Xs×100≤3.5), the peeling force between the peeling film and the adhesive layer is uniform, thereby achieving good removal of the peeling film.

Benefits of technology

The release film is well peeled off from the adhesive layer, avoiding the situation of breakage of the adhesive layer, and improving the stability and application efficiency of the laminated body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731568A_ABST
    Figure CN119731568A_ABST
Patent Text Reader

Abstract

Provided is an optical laminate in which a release film can be satisfactorily peeled off from an adhesive layer. The optical laminate includes an optical film, an adhesive layer, and a release film in this order. The release film has a release surface containing a siloxane compound on the side in contact with the adhesive layer. The peeling treatment surface of the peeling film satisfies the relationship represented by formula (1). Ys / Xs * 100 < = 3.5 (1) [In formula (1), Xs represents the intensity of the peak Ps having the maximum binding energy in the range of 96 eV to 108 eV in the XPS spectrogram (Sr) of the peeling treatment surface, and Ys represents the intensity of the XPS spectrogram (Sr) at the binding energy (Es + 2) eV when Es [eV] is the binding energy at the peak Ps. ]
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body. Background Art

[0002] It is known that an optical film such as a polarizing plate is used in a display device such as a liquid crystal display device and an organic EL display device. The optical film is incorporated into a display device by being bonded to a display panel of the display device using an adhesive layer. Therefore, it is known that when manufacturing a display device, a laminated body having an adhesive layer and a release film sequentially laminated on one surface of the optical film is prepared, and the optical film is bonded to a display panel or the like using the adhesive layer exposed by peeling off a spacer from the laminated body.

[0003] The laminate can be obtained, for example, by laminating an optical film and an adhesive layer with a release film in which an adhesive layer is formed on a release film. The adhesive layer with a release film can be obtained by peeling off one release film from an adhesive sheet in which an adhesive layer is formed on a release film and another release film is laminated on the adhesive layer. Patent Document 1 discloses an adhesive sheet having release films on both sides of an adhesive layer used for laminating optical components.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-52073 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In the adhesive sheet, the peeling force between one release film and the adhesive layer is relatively small, and the peeling force between the other release film and the adhesive layer is relatively large. As a result, the release films on both sides can be peeled off from the adhesive layer in sequence, and the adhesive layer is prevented from breaking when the release films are peeled off. Therefore, in the case of obtaining a laminated body by laminating the adhesive layer and the release film contained in the adhesive sheet on the optical film, the release film with relatively small peeling force (hereinafter sometimes referred to as "light release film") is peeled off from the adhesive sheet when the optical film is laminated to obtain an adhesive layer with a release film having an adhesive layer and a release film with relatively large peeling force (hereinafter sometimes referred to as "heavy release film") .

[0009] When a polarizing plate is used in a display device, a heavy release film is sometimes peeled off from a laminated body while a laminated body having an adhesive layer with a release film is fixed on an adsorption plate. If the heavy release film is to be peeled off by this method, the laminated body may bulge from the adsorption plate and the heavy release film may not be peeled off from the adhesive layer.

[0010] An object of the present invention is to provide an optical laminate in which a release film can be well released from a pressure-sensitive adhesive layer.

[0011] Means for solving problems

[0012] The present invention provides the following optical layered body.

[0013] [1] An optical laminate comprising an optical film, an adhesive layer and a release film in this order,

[0014] The release film has a release-treated surface containing a silicone compound on the side in contact with the adhesive layer.

[0015] The release-treated surface of the release film satisfies the relationship of the following formula (1).

[0016] Ys / Xs×100≤3.5 (1)

[0017] [In formula (1),

[0018] Xs represents the intensity of the largest peak Ps in the range of binding energy of 96 eV or more and 108 eV or less in the XPS spectrum (Sr) of the peeling-treated surface.

[0019] Ys represents the intensity of the XPS spectrum (Sr) at the binding energy (Es+2) eV when the binding energy at the peak Ps is Es [eV].]

[0020] [2] The optical laminate according to [1], wherein the surface of the pressure-sensitive adhesive layer on the release film side satisfies the relationship of the following formula (2).

[0021] Ya / Xa×100≥2.0 (2)

[0022] [In formula (2),

[0023] Xa represents the intensity of the maximum peak Pa in the range of binding energy of 96 eV or more and 108 eV or less in the XPS spectrum (Sa) of the surface of the pressure-sensitive adhesive layer on the release film side,

[0024] Ya represents the intensity of the XPS spectrum (Sa) at a binding energy of (Ea+2) eV when the binding energy at the peak Pa is Ea [eV].]

[0025] [3] The optical layered body according to [1] or [2], wherein the thickness of the optical film is 120 μm or less.

[0026] [4] The optical layered body according to any one of [1] to [3], wherein the optical film is a polarizing plate including at least a linear polarizing layer.

[0027] [5] The optical layered body according to [4], wherein the polarizing plate further includes a retardation layer.

[0028] [6] The optical layered body according to [4] or [5], wherein the optical film includes a surface protective film provided so as to be removable from the polarizing plate.

[0029] Effects of the Invention

[0030] According to the optical laminate of the present invention, the release film can be peeled off from the pressure-sensitive adhesive layer in a good manner. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic cross-sectional view showing an optical layered body according to one embodiment of the present invention.

[0032] Figure 2 This is a schematic cross-sectional view showing a method for producing an optical layered body according to one embodiment of the present invention. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the present invention will be described with reference to the drawings; however, the present invention is not limited to the following embodiments.

[0034] (Optical laminate)

[0035] Figure 1 Schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate 1 includes an optical film 11 , a first adhesive layer 12 (adhesive layer), and a first release film 15 (release film) in this order. The first adhesive layer 12 is usually in direct contact with the optical film 11 and the first release film 15 .

[0036] The optical film 11 may be a polarizing plate including at least a linear polarizing layer, or may be a polarizing plate including a polarizing plate and a phase difference layer. The optical film 11 may include a surface protective film provided so as to be releasable from the polarizing plate.

[0037] The first release film 15 has a release-treated surface containing a siloxane compound on the side in contact with the first pressure-sensitive adhesive layer 12. The release-treated surface of the first release film 15 satisfies the relationship of the following formula (1).

[0038] Ys / Xs×100≤3.5 (1)

[0039] [In formula (1),

[0040] Xs represents the intensity of the largest peak Ps in the range of binding energy of 96 eV to 108 eV in the XPS spectrum (Sr) of the peeling-treated surface.

[0041] Ys represents the intensity of the XPS spectrum (Sr) at the binding energy (Es+2) eV when the binding energy at the peak Ps is set to Es [eV]. ]

[0042] The binding energy (Es+2) eV means the binding energy at a position shifted by 2 eV to the higher energy side from the position of the binding energy Es at the peak Ps in the XPS spectrum (Sr).

[0043] The largest peak Ps in the range of binding energy of 96 eV or more and 108 eV or less is considered to be mainly derived from the structure (I) in which two O atoms are bonded to Si atoms of the siloxane compound contained in the release treatment surface. The intensity Ys of the XPS spectrum (Sr) at the binding energy (Es+2) eV is considered to be mainly derived from the structure (II) in which three or more O atoms are bonded to Si atoms of the siloxane compound contained in the release treatment surface. The structure (I) is considered to be derived from the structure of the siloxane compound as the main agent of the release agent composition used to form the release treatment surface (release treatment layer) of the release film. The structure (II) is considered to be derived from the structure of the siloxane compound as an additive added to the release agent composition in order to obtain a release film having a relatively large release force. Therefore, the left side (Ys / Xs×100) in the formula (1) can represent the ratio of the content of the above-mentioned siloxane compound as an additive in the siloxane compound on the release treatment surface of the first release film 15 relative to the content of the above-mentioned siloxane compound as the main agent.

[0044] As described later, the optical laminate 1 can be produced, for example, by [i] laminating the optical film 11 on the second release film 25 ( Figure 2), after the first adhesive layer 12 on the optical laminate 1 is peeled off, the second release film 25 is peeled off, and [ii] the first release film 15 having a smaller release force than the second release film 25 is laminated on the first adhesive layer 12 exposed by the peeling off of the second release film 25. It is considered that in the optical laminate 1 obtained through such a process, as the release film is replaced by the pasting, a small amount of the siloxane compound constituting the release-treated surface (release-treated layer) of the second release film 25 is attached to the first adhesive layer 12, and the siloxane compound attached to the first adhesive layer 12 is also attached to the release-treated surface of the first release film 15. Therefore, it is considered that, for example, even if the release-treated surface (release-treated layer) of the first release film 15 does not contain the siloxane compound having the structure (II) that imparts a relatively large release force to the release film, if the release-treated surface (release-treated layer) of the second release film 25 is formed of a release agent composition containing the siloxane compound having the structure (II), the siloxane compound having the structure (II) contained in the release-treated surface of the second release film 25 will adhere to the release-treated surface of the first release film 15 by replacing the second release film 25 with the first release film 15. Therefore, it is considered that, for example, in the optical laminate 1 manufactured by replacing the release films as described above, the release-treated surface of the first release film 15 satisfies the relationship of the above-mentioned formula (1).

[0045] Ys / Xs×100 in the formula (1) may be 3.50 or less, 3.45 or less, or 3.40 or less. Ys / Xs×100 in the formula (1) is usually 0.1 or more, 1.0 or more, 2.0 or more, or 2.6 or more. The intensity Xs and the intensity Ys can be measured by the method described in the examples described later.

[0046] It is considered that the optical laminate 1 has a release film with a small release force by making the release-treated surface of the first release film 15 satisfy the relationship of formula (1). Therefore, when the first release film 15 is peeled off from the optical laminate 1 in a state where the optical film 11 side of the optical laminate 1 is fixed to the adsorption plate, the first release film 15 is easily separated between the first adhesive layer 12 and the first release film 15.

[0047] In the optical laminate 1 , it is preferred that the surface of the first pressure-sensitive adhesive layer 12 on the first release film 15 side satisfies the relationship of the following formula (2).

[0048] Ya / Xa×100≥2.0 (2)

[0049] [In formula (2),

[0050] Xa represents the intensity of the maximum peak Pa in the range of binding energy of 96 eV or more and 108 eV or less in the XPS spectrum (Sa) of the surface of the first pressure-sensitive adhesive layer 12 on the first release film 15 side.

[0051] Ya represents the intensity of the above XPS spectrum (Sa) at the binding energy (Ea+2) eV when the binding energy at the peak Pa is set to Ea [eV].]

[0052] The binding energy (Ea+2) eV means the binding energy at a position shifted 2 eV toward the higher energy side from the position of the binding energy Ea at the peak Pa in the XPS spectrum (Sa).

[0053] The maximum peak Pa in the range of binding energy of 96 eV or more and 108 eV or less is considered to be mainly derived from the structure (I) in which two O atoms are bonded to Si atoms of the siloxane compound attached to the surface of the first release film 15 side of the first adhesive layer 12. The intensity of the XPS spectrum (Sa) at the binding energy (Ea+2) eV is considered to be mainly derived from the structure (II) in which three or more O atoms are bonded to Si atoms of the siloxane compound attached to the surface of the first release film 15 side of the first adhesive layer 12. The siloxane compounds that give rise to the structures (I) and (II) are as described above.

[0054] It is considered that the siloxane compound contained in the release-treated surface (release-treated layer) of the release film laminated on the surface in the manufacturing process of the optical laminate 1 is slightly attached to the surface of the first adhesive layer 12 on the first release film 15 side. It is considered that, as described above, when the optical laminate 1 is manufactured with the release film being attached and replaced, the second release film 25 ( Figure 2 ). Therefore, when the release surface of the second release film 25 is formed of a release agent composition containing a siloxane compound having structure (II), even if the second release film 25 is replaced by the first release film 15, the siloxane compound having structure (II) contained in the release surface of the second release film 25 remains on the surface of the first adhesive layer 12 on the first release film 15 side. Therefore, it is considered that, for example, in the optical laminate 1 manufactured by replacing the release films as described above, the surface of the first adhesive layer 12 on the first release film 15 side satisfies the relationship of the above formula (2).

[0055] Ya / Xa×100 in the formula (2) may be 2.0 or more, 2.5 or more, 3.0 or more, or 3.4 or more. Ya / Xa×100 in the formula (2) is usually 20 or less, 15 or less, 10 or less, or 6.6 or less. The strength Xa and the strength Ya can be measured by the method described in the examples described later.

[0056] It is considered that the optical laminate 1 is manufactured as described above with the peeling film being attached and replaced by making the surface of the first adhesive layer 12 on the first release film 15 side satisfy the relationship of formula (2). Therefore, when the first release film 15 is peeled off from the optical laminate 1 in a state where the optical film 11 side of the optical laminate 1 is fixed to the adsorption plate, the first release film 15 can be easily separated between the first adhesive layer 12 and the first release film 15.

[0057] For the optical laminate 1, the first release film 15 is peeled off, and the optical film 11 can be attached to the display element of the display device by using the exposed first adhesive layer 12. The display device is not particularly limited, and a liquid crystal display device and an organic EL display device can be cited. The display device can be a portable terminal such as a smart phone and a tablet computer, and can also be a television, a digital photo frame, an electronic billboard, a measuring instrument, a measuring instrument, an office equipment, a medical device, an electronic computer device, etc.

[0058] (Method for producing optical laminate)

[0059] Figure 2 1 is a schematic cross-sectional view showing a method for manufacturing an optical laminate according to an embodiment of the present invention. The method for manufacturing an optical laminate according to the present embodiment is a method for manufacturing an optical laminate 1 which sequentially includes an optical film 11, a first adhesive layer 12, and a first release film 15. Hereinafter, the method for manufacturing the optical laminate 1 will be described, but the optical laminate manufactured by the manufacturing method is not limited thereto.

[0060] The method for manufacturing the optical laminate 1 includes:

[0061] A step of laminating the first adhesive layer 12 side of the adhesive layer 21 with a release film having the first adhesive layer 12 on the second release treated surface of the second release film 25 to the optical film 11 to obtain the first laminate 2 ( Figure 2 (c))

[0062] A step of peeling off the second release film 25 from the first laminate 2 ( Figure 2 (d)) and

[0063] A step of laminating the first release film 15 on the first adhesive layer 12 exposed by peeling off the second release film 25 to obtain the second laminate 3 ( Figure 2 (e)).

[0064] In the method for producing the optical layered body 1 described above, both the first release-treated surface and the second release-treated surface contain a polysiloxane compound.

[0065] In the above-mentioned method for manufacturing the optical laminate 1, the peeling force between the first release film 15 and the first adhesive layer 12 is preferably smaller than the peeling force between the second release film 25 and the first adhesive layer 12. Thus, it is easy to obtain an optical laminate 1 in which the first release film 15 is easily peeled off in a state where the optical film 11 side of the optical laminate 1 is fixed to an adsorption plate.

[0066] In the method for producing the optical layered body 1,

[0067] The second release treated surface of the second release film 25 released from the first laminate 2 and the first release treated surface of the first release film 15 released from the second laminate 3 may satisfy the relationship of the following formula (3) and formula (4).

[0068] Ys2 / Xs2>Ys1 / Xs1 (3)

[0069] Ys1 / Xs1×100≤3.5 (4)

[0070] [In formula (3) and formula (4),

[0071] Xs2 represents the intensity of the largest peak Ps2 in the range of binding energy of 96 eV to 108 eV in the XPS spectrum (Sr2) of the second peeling-treated surface,

[0072] Ys2 represents the intensity of the XPS spectrum (Sr2) at the binding energy (Es2+2) [eV] when the binding energy at the peak Ps2 is set to Es2 [eV].

[0073] Xs1 represents the intensity of the largest peak Ps1 in the range of binding energy of 96 eV to 108 eV in the XPS spectrum (Sr1) of the first peeling-treated surface,

[0074] Ys1 represents the intensity of the XPS spectrum (Sr1) at the binding energy (Es1+2) [eV] when the binding energy at the peak Ps1 is set to Es1 [eV].

[0075] The binding energy (Es2+2) eV means the binding energy at a position shifted by 2 eV to the higher energy side from the position of the binding energy Es2 at the peak Ps2 in the XPS spectrum (Sr2).

[0076] In the above formula (3), the maximum peak Ps2 in the range of binding energy of 96 eV to 108 eV is considered to be mainly derived from the structure (I) in which two O atoms are bonded to the Si atom of the siloxane compound attached to the second peeling treatment surface of the second peeling film 25. The intensity of the XPS spectrum (Sr2) at the binding energy (Es2+2) eV is considered to be mainly derived from the structure (II) in which three or more O atoms are bonded to the Si atom of the siloxane compound attached to the second peeling treatment surface of the second peeling film 25. The siloxane compounds that bring about the structures (I) and (II) are as described above. The second peeling treatment surface that satisfies the above formula (3) is considered to be formed by a peeling agent composition that contains a siloxane compound having the structure (I) and a siloxane compound having the structure (II) and bringing a relatively large peeling force to the peeling film.

[0077] In the above formula (3) and formula (4), the binding energy (Es1+2), the peak Ps1, and the intensity Ys2 of the XPS spectrum (Sr1) at the binding energy (Es1+2) eV are respectively as described in the binding energy (Es+2), the peak Ps, and the intensity Ys of the above formula (1). The siloxane compound (a siloxane compound as an additive having structure (II) and providing a relatively large peeling force) constituting the second peeling surface of the second peeling film 25 is attached in a trace amount to the first peeling treated surface of the first peeling film 15 along with the replacement of the second peeling film 25 with the first peeling film 15. Therefore, the first peeling treated surface is considered to satisfy the relationship of the above formula (4), and the optical laminate 1 satisfying the relationship of the above-described formula (1) can be manufactured.

[0078] It is considered that the optical laminate 1 is manufactured by satisfying the relationship of the above-mentioned formula (3) and formula (4) in the manufacturing method of the optical laminate 1, accompanied by the sticking replacement from the second release film 25 with relatively large release force to the first release film 15 with relatively small release force. Therefore, according to the above-mentioned manufacturing method of the optical laminate 1, it is possible to manufacture an optical laminate 1 in which the first release film 15 can be easily separated and peeled off between the first adhesive layer 12 and the first release film 15 in a state where the optical film 11 side of the optical laminate 1 is fixed to the adsorption plate.

[0079] The value obtained by multiplying Ys2 / Xs2 by 100 in formula (3) (Ys2 / Xs2×100) may be 3.6 or more, 4.0 or more, or 5.0 or more, or 15.0 or less, 12.5 or less, or 10.0 or less. The strength Xs2 and the strength Ys2 may be measured by the method described in the examples described later.

[0080] Ys1 / Xs1×100 in formula (4) may be 3.50 or less, 3.45 or less, or 3.40 or less, and is usually 0.1 or more, 1.0 or more, 2.0 or more, or 2.6 or more. The strength Xs1 and the strength Ys1 can be measured by the method described in the examples described below.

[0081] In the method for producing the optical layered body 1,

[0082] The second exposed surface, which is the surface of the first adhesive layer 12 exposed by peeling off the second release film 25 from the first laminate 2, and the first exposed surface, which is the surface of the first adhesive layer 12 exposed by peeling off the first release film 15 from the second laminate 3, can satisfy the relationship of the following formula (5) and formula (6). The second exposed surface is the surface of the first adhesive layer 12 on the second release film 25 side, and the first exposed surface is the surface of the first adhesive layer 12 on the first release film 15 side.

[0083] Ya2 / Xa2>Ya1 / Xa1 (5)

[0084] Ya1 / Xa1×100≥2.0 (6)

[0085] [In formula (5) and formula (6),

[0086] Xa2 represents the intensity of the largest peak Pa2 in the range of binding energy of 96 eV to 108 eV in the XPS spectrum (Sa2) of the second exposed surface,

[0087] Ya2 represents the intensity of the XPS spectrum (Sa2) at a binding energy of (Ea2+2) eV when the binding energy at the peak Pa2 is set to Ea2 [eV].

[0088] Xa1 represents the intensity of the largest peak Pa1 in the binding energy range of 96 eV to 108 eV in the XPS spectrum (Sa1) of the first exposed surface,

[0089] Ya1 represents the intensity of the above XPS spectrum (Sa1) at the binding energy (Ea1+2) eV when the binding energy at the peak Pa1 is set to Ea1 [eV]. ]

[0090] The binding energy (Ea2+2) eV means the binding energy at a position shifted by 2 eV to the higher energy side from the position of the binding energy Ea2 at the peak Pa2 in the XPS spectrum (Sa2).

[0091] In the above formula (5), the maximum peak Pa2 in the range of binding energy of 96 eV or more and 108 eV or less is considered to be mainly derived from the structure (I) in which two O atoms are bonded to Si atoms of the siloxane compound attached to the second exposed surface of the first adhesive layer 12. The intensity of the XPS spectrum (Sr2) at the binding energy (Es2+2) eV is considered to be mainly derived from the structure (II) in which three or more O atoms are bonded to Si atoms of the siloxane compound attached to the second exposed surface. It is considered that the siloxane compound contained in the second release treated surface of the second release film is slightly attached to the second exposed surface.

[0092] In the above formula (5) and formula (6), the binding energy (Ea1+2), the peak Pa1, and the intensity Ya1 of the XPS spectrum (Sa1) at the binding energy (Ea1+2) eV are respectively as described in the binding energy (Ea+2), the peak Pa, and the intensity Ya in the above formula (2). Although the manufacturing method of the optical laminate 1 is accompanied by the sticking replacement from the second release film 25 to the first release film 15, the siloxane compound (a siloxane compound as an additive having structure (II) and providing a relatively large release force) constituting the second release treated surface of the second release film 25 remains on the first exposed surface of the first adhesive layer 12. Therefore, it is considered that, by the sticking replacement of the above release film, the second exposed surface and the first exposed surface satisfy the relationship of formula (5), and the first exposed surface satisfies the relationship of formula (6).

[0093] It is considered that the optical laminate 1 is manufactured by satisfying the relationship of the above-mentioned formula (5) and formula (6) in the manufacturing method of the optical laminate 1, accompanied by the sticking replacement from the second release film 25 with relatively large release force to the first release film 15 with relatively small release force. Therefore, according to the above-mentioned manufacturing method of the optical laminate 1, it is possible to manufacture an optical laminate 1 in which the first release film 15 can be easily separated and peeled off between the first adhesive layer 12 and the first release film 15 in a state where the optical film 11 side of the optical laminate 1 is fixed to the adsorption plate.

[0094] The value obtained by multiplying Ya2 / Xa2 by 100 in formula (5) (Ya2 / Xa2×100) may be, for example, less than 20, less than 18, or less than 15, or more than 6.7, more than 7.0, or more than 8.0. The strength Xa2 and the strength Ya2 may be measured by the method described in the examples described later.

[0095] Ya1 / Xa1×100 in formula (6) may be 2.0 or more, 2.5 or more, 3.0 or more, or 3.4 or more, and may be 20 or less, 15 or less, 10 or less, or 6.6 or less. The strength Xa1 and the strength Ya1 may be measured by the method described in the examples described below.

[0096] The method for producing the optical laminate 1 preferably further comprises the step of peeling off the third release film 26 from the release-treated surface of the adhesive sheet 20 on which the third release film 26 is laminated on the first adhesive layer 12 side of the adhesive layer with a release film, thereby obtaining the adhesive layer 21 with a release film ( Figure 2 (a) and (b)). The pressure-sensitive adhesive sheet 20 has a layer structure of second release film 25 / first pressure-sensitive adhesive layer 12 / third release film 26 .

[0097] In the adhesive sheet 20 used above, the peeling force between the third release film 26 and the first adhesive layer 12 is preferably smaller than the peeling force between the second release film 25 and the first adhesive layer 12. In the case where the peeling forces of the release films provided on both sides of the first adhesive layer 12 in the adhesive sheet 20 are the same, if the release films are intended to be peeled off, the first adhesive layer 12 may be torn and the release films may not be peeled off well. By making the peeling forces different between the second release film 25 and the third release film 26 provided on both sides of the first adhesive layer 12 as described above, it is possible to suppress the tearing of the first adhesive layer 12 when peeling the third release film 26 from the adhesive sheet 20. As a result, the third release film 26 can be peeled off well from the adhesive sheet 20 to obtain the adhesive layer 21 with the release film.

[0098] The first laminate 2 ( Figure 2 (c)). The first laminate 2 has a layer structure of optical film 11 / first adhesive layer 12 / second release film 25. The second release film 25 is peeled off from the first laminate 2 ( Figure 2 (d)), the first release-treated surface of the first release film 15 is attached to the exposed first adhesive layer 12, thereby obtaining a second laminate 3 ( Figure 2 (e)). The second laminate 3 has a layer structure of an optical film 11 / a first pressure-sensitive adhesive layer 12 / a first release film 15. The second laminate 3 may be the optical laminate 1.

[0099] Hereinafter, the details of each layer constituting the optical layered body will be described.

[0100] (First release film (release film))

[0101] The first release film 15 is provided so as to be releasable relative to the first adhesive layer 12 of the optical laminate 1, and covers and protects the first adhesive layer 12. The first release film 15 may include a substrate layer and a release treatment layer constituting a release treatment surface. The substrate layer may also be a resin film. The resin film may be, for example, a film using a resin material described as a thermoplastic resin for forming a protective film as a protective layer described later.

[0102] The release treatment layer of the first release film 15 can be formed using a release agent composition containing a siloxane compound. The release agent composition preferably contains a siloxane compound (main agent) having a structure (I) in which two O atoms are bonded to a Si atom, and does not contain a siloxane compound (additive) having a structure (II) in which three or more O atoms are bonded to a Si atom. Thus, the first release film 15 can be peeled off from the first adhesive layer 12 of the optical laminate 1 with a small peeling force.

[0103] Examples of the siloxane compound having structure (I) include siloxane compounds having dimethyl polysiloxane as a basic skeleton. Examples of the siloxane compound having structure (II) include silicone resins. Examples of the silicone resin include silicone resins containing a monofunctional siloxane unit [R3SiO 1 / 2 ] and as a tetrafunctional siloxane unit [SiO 4 / 2 The three R's in the M unit each independently represent a hydrogen atom, a hydroxyl group, or an organic group, and at least one of the three R's is preferably a hydroxyl group or a vinyl group, and more preferably a vinyl group.

[0104] The release agent composition for forming the release treatment layer of the first release film 15 may contain a solvent such as an organic solvent, a crosslinking agent, a catalyst, various additives, and the like in addition to the siloxane compound having the structure (I).

[0105] The first release film 15 can be obtained by applying a release agent composition on a substrate layer and drying the release agent composition. Examples of the method for applying the release agent composition include bar coating, knife coating, roll coating, blade coating, die coating, and gravure coating.

[0106] (First adhesive layer (adhesive layer))

[0107] The first adhesive layer 12 can be formed using an adhesive composition. The adhesive composition is a substance that exhibits adhesiveness by being attached to an adherend, and is a substance called a so-called pressure-sensitive adhesive.

[0108] The thickness of the first adhesive layer 12 is preferably 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more, and is preferably 100 μm or less, 80 μm or less, 75 μm or less, or 70 μm or less.

[0109] The first adhesive layer 12 can be formed, for example, by applying the adhesive composition itself or an organic solvent dilution of the adhesive composition on the release-treated surface of a release film (e.g., the second release film 25) and drying it. Examples of methods for applying the adhesive composition or its organic solvent dilution include bar coating, knife coating, roll coating, blade coating, die coating, and gravure coating.

[0110] The adhesive composition can use a known adhesive composition with excellent optical transparency. As a known adhesive composition, for example, an adhesive composition containing a base polymer such as a (meth) acrylic polymer, a urethane polymer, a silicone polymer, and a polyvinyl ether can be used. In addition, the adhesive composition can also be an active energy ray-curable adhesive or a thermosetting adhesive. Among them, an adhesive composition with an acrylic resin as a base polymer that is excellent in transparency, adhesion, re-peelability (reprocessability), weather resistance, heat resistance, etc. is suitable. The first adhesive layer is preferably composed of an adhesive composition containing a (meth) acrylic polymer, a crosslinking agent, and a silane coupling agent, and may also contain other components. The so-called "(meth) acrylic" means at least one of acrylic and methacrylic. The same is true in other terms marked with "(meth)".

[0111] The (meth)acrylic polymer preferably contains a structural unit derived from an alkyl (meth)acrylate (monomer) having an alkyl group with a carbon number of 1 or more and 24 or less. The alkyl group may be linear or branched. As the above-mentioned alkyl (meth)acrylate having an alkyl group, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, etc. can be cited. The above-mentioned alkyl (meth)acrylate can be used alone or in combination of two or more.

[0112] The content of the structural unit derived from the alkyl (meth)acrylate having an alkyl group relative to all structural units of the (meth)acrylic polymer is preferably 30% by mass or more, 40% by mass or more, or 50% by mass or more, and may be 99% by mass or less, 97% by mass or less, or 90% by mass or less.

[0113] The (meth)acrylic polymer may contain a structural unit derived from a monomer having a polar functional group. Examples of the polar functional group include a hydroxyl group, a carboxyl group, an amino group, an epoxy group, and an amide group.

[0114] Examples of the monomer having a polar functional group include:

[0115] (Meth)acrylates having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-(2-hydroxyethoxy)ethyl (meth)acrylate, 2-chloro-2-hydroxypropyl (meth)acrylate or 3-chloro-2-hydroxypropyl (meth)acrylate, and diethylene glycol mono(meth)acrylate;

[0116] Ethylenically unsaturated carboxylic acids such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, citraconic acid, and β-carboxyethyl (meth)acrylate;

[0117] (Meth)acrylates having an amino group such as aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminoethyl (meth)acrylate;

[0118] (Meth)acrylates having an epoxy group, such as (3,4-epoxycyclohexyl)methyl (meth)acrylate and glycidyl (meth)acrylate;

[0119] (Meth)acrylates having an amide group, such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, and N-hydroxymethyl (meth)acrylamide;

[0120] (Meth)acryloylmorpholine, vinylcaprolactam, N-vinyl-2-pyrrolidone, vinylpyridine, tetrahydrofurfuryl (meth)acrylate and other monomers having a heterocyclic group; etc. The monomer having a polar functional group may be used alone or in combination of two or more.

[0121] The content of the structural unit derived from the monomer having a polar functional group based on all structural units of the (meth)acrylic polymer is preferably 5% by mass or less, and may be 2% by mass or less, or 1% by mass or less.

[0122] The (meth)acrylic polymer can be obtained by mixing the above-mentioned monomers, adding a polymerization initiator, etc., and polymerizing the monomers. The polymerization initiator can be selected according to the polymerization method, and examples thereof include a cationic polymerization initiator and a free radical polymerization initiator. When the polymerization method is photopolymerization, a photopolymerization initiator can be used. One or more photopolymerization initiators can be used.

[0123] Examples of crosslinking agents that may be included in the adhesive composition include isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, and ammonium salt crosslinking agents.

[0124] Examples of the silane coupling agent that may be included in the adhesive include organic silicon compounds having at least one alkoxysilyl group in the molecule. Examples of the silane coupling agent include:

[0125] Silicon compounds containing polymerizable unsaturated groups such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane;

[0126] Silicon compounds with epoxy structure such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane;

[0127] Silicon compounds containing mercapto groups such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane;

[0128] Silicon compounds containing amino groups such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane;

[0129] 3-Chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, or a condensate of at least one of them and an alkyl group-containing silicon compound such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, or ethyltrimethoxysilane.

[0130] (Second release film)

[0131] The second release film 25 covers and protects the first adhesive layer 12 included in the first laminate 2 produced when manufacturing the optical laminate 1. The second release film 25 may be a film included in the adhesive sheet 20 and coated with an adhesive composition for forming the first adhesive layer 12 when the first adhesive layer 12 is obtained.

[0132] The second release film 25 may include a base layer and a release treatment layer constituting a release treatment surface. The base layer may also be a resin film. The resin film may be, for example, a film using a resin material described as a thermoplastic resin for forming a protective film as a protective layer described later.

[0133] The release treatment layer of the second release film 25 can be formed by using a release agent composition containing a siloxane compound. The release agent composition preferably contains a siloxane compound having structure (I) and a siloxane compound having structure (II). As these siloxane compounds, the siloxane compounds described in the first release film can be cited. By using the above-mentioned release agent composition to form the release treatment layer of the second release film 25, the peeling force between the second release film 25 and the first adhesive layer 12 can be increased. As a result, in the adhesive sheet 20, the peeling force between the first adhesive layer 12 and the second release film 25 is greater than the peeling force between the first adhesive layer 12 and the third release film 26, and the third release film 26 can be easily peeled off from the adhesive sheet 20.

[0134] The release agent composition used to form the release treatment layer of the second release film 25 may contain a solvent such as an organic solvent, a crosslinking agent, a catalyst, various additives, etc. in addition to the above-mentioned siloxane compound. The second release film 25 can be obtained by applying the release agent composition on the substrate layer and drying it. The method for applying the release agent composition can be the method described in the first release film 15.

[0135] (3rd release film)

[0136] The third release film 26 may be a film included in the pressure-sensitive adhesive sheet 20 and laminated on the first pressure-sensitive adhesive layer 12 formed on the second release film 25 when the pressure-sensitive adhesive sheet 20 is obtained. Examples of the third release film 26 include the release films described for the first release film 15.

[0137] (Adhesive sheet)

[0138] The adhesive sheet 20 may have a layer structure of second release film 25 / first adhesive layer 12 / third release film 26. By making the adhesive sheet 20 include the second release film 25 and the third release film 26, the peeling force between the third release film 26 and the first adhesive layer 12 can be made smaller than the peeling force between the second release film 25 and the first adhesive layer 12.

[0139] The adhesive sheet 20 can be obtained, for example, by the following steps. First, the adhesive composition itself or the organic solvent dilution of the adhesive composition for forming the first adhesive layer 12 is applied to the release treatment surface of one of the second release film 25 and the third release film 26, and dried as needed to form a coating layer. Then, the other release film of the second release film 25 and the third release film 26 is laminated on the coating layer so that the release treatment surface side is the coating layer side, and dried as needed to obtain an adhesive sheet. The adhesive composition or its organic solvent dilution is preferably applied to the second release film 25. The coating layer formed on one release film can be the first adhesive layer 12, and the first adhesive layer 12 can be formed from the coating layer by drying treatment before or after laminating another release film.

[0140] Examples of the method for applying the pressure-sensitive adhesive composition or its organic solvent-diluted solution include bar coating, knife coating, roll coating, blade coating, die coating, and gravure coating.

[0141] (Optical film)

[0142] The linear polarizing layer can be cited; a linear polarizing plate having a protective layer on one or both sides of the linear polarizing layer; a circular polarizing plate comprising a linear polarizing layer or a linear polarizing plate and one or more phase difference layers; a polarizing plate with a surface protective film having a surface protective film on one side of a polarizing plate such as a linear polarizing plate and a circular polarizing plate; a phase difference layer; a phase difference plate having a protective layer on one or both sides of the phase difference layer; a reflective film; a semi-transmissive reflective film; a brightness enhancement film; a film with an anti-glare function, etc., and one or more of them can also be used in combination. The optical film preferably comprises at least a linear polarizing layer, and more preferably comprises a linear polarizing plate or a circular polarizing plate. At least one of the phase difference layers contained in the circular polarizing plate is usually a λ / 4 phase difference layer.

[0143] The thickness of the optical film 11 is preferably 150 μm or less, and may be 140 μm or less, 130 μm or less, or 120 μm or less, and is usually 10 μm or more, and may be 20 μm or more. When the thickness of the optical film 11 is as small as described above, if the optical film side is fixed to the adsorption plate and the release film is intended to be peeled off from the optical laminate, the optical laminate bulges from the adsorption plate, and there is a situation where the adhesive layer and the release film cannot be separated. According to the optical laminate of this embodiment, even when the thickness of the optical film 11 is small, the first release film 15 and the first adhesive layer 12 can be separated and peeled off from the optical laminate.

[0144] (Linear polarization layer)

[0145] The linear polarizing layer has the property of transmitting linear polarized light having a vibration plane orthogonal to the absorption axis when non-polarized light is incident. The linear polarizing layer may be a polyvinyl alcohol-based resin film (hereinafter sometimes referred to as a "PVA-based film") in which iodine is adsorbed and oriented, or a film including a liquid crystal polarizing layer formed by applying a composition including a compound having absorption anisotropy and liquid crystal to a substrate film. The compound having absorption anisotropy and liquid crystal may be a mixture of a pigment having absorption anisotropy and a compound having liquid crystal, or may be a pigment having absorption anisotropy and liquid crystal.

[0146] As the linear polarizing layer of the PVA film, for example, a film obtained by dyeing and stretching a PVA film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, etc., can be cited. If necessary, the PVA film oriented by iodine adsorption by dyeing can be treated with an aqueous boric acid solution, and then a washing step of washing away the aqueous boric acid solution can be performed. Each step can adopt a known method.

[0147] Polyvinyl alcohol resin (hereinafter sometimes referred to as "PVA resin") can be produced by saponifying polyvinyl acetate resin. Polyvinyl acetate resin may be a copolymer of vinyl acetate and other monomers copolymerizable with vinyl acetate, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.

[0148] The saponification degree of PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. PVA resin can be modified, for example, polyvinyl formal, polyvinyl acetal, etc. modified by aldehydes can also be used. The average polymerization degree of PVA resin is usually about 1000 to 10000, preferably about 1500 to 5000. The saponification degree and average polymerization degree of PVA resin can be calculated according to JIS K 6726 (1994). If the average polymerization degree is less than 1000, it is difficult to obtain the preferred polarization performance, and if it is greater than 10000, the film processability is poor.

[0149] The method for manufacturing a linear polarizing layer as a PVA film may include the following steps, namely, preparing a substrate film, applying a solution of a resin such as a PVA resin on the substrate film, and performing drying to remove the solvent to form a resin layer on the substrate film. It should be noted that a primer layer may be formed in advance on the surface of the substrate film on which the resin layer is formed. As the substrate film, a film using a resin material described as a thermoplastic resin for forming a protective film as a protective layer described later may be used. As the material of the primer layer, a resin obtained by cross-linking a hydrophilic resin used in the linear polarizing layer may be cited.

[0150] Then, the amount of solvent such as water in the resin layer is adjusted as needed, and then the base film and the resin layer are uniaxially stretched, and then the resin layer is dyed with iodine so that the iodine is adsorbed and oriented in the resin layer. Then, the resin layer adsorbed and oriented with iodine is treated with an aqueous boric acid solution as needed, and then a washing step of washing away the aqueous boric acid solution is performed. Thus, a PVA film that becomes a linear polarizing layer and a resin layer adsorbed and oriented with iodine is manufactured. Each step can adopt a known method.

[0151] The amount of boric acid in the boric acid aqueous solution in which the PVA film or resin layer in which iodine is adsorbed and oriented is treated is generally about 2 to 15 parts by mass per 100 parts by mass of water, preferably about 5 to 12 parts by mass. The boric acid aqueous solution preferably contains potassium iodide. The amount of potassium iodide in the boric acid aqueous solution is generally about 0.1 to 15 parts by mass per 100 parts by mass of water, preferably about 5 to 12 parts by mass. The immersion time in the boric acid aqueous solution is generally about 60 to 1200 seconds, preferably about 150 to 600 seconds, and more preferably about 200 to 400 seconds. The temperature of the boric acid aqueous solution is generally above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0152] The uniaxial stretching of the PVA film, the substrate film and the resin layer can be performed before dyeing, during dyeing, during the boric acid treatment after dyeing, or during these multiple stages. The PVA film, the substrate film and the resin layer can be uniaxially stretched along the MD direction (film transport direction). In this case, they can be stretched uniaxially between rollers with different peripheral speeds, or they can be stretched uniaxially using hot rollers. In addition, the PVA film, the substrate film and the resin layer can also be uniaxially stretched along the TD direction (a direction perpendicular to the film transport direction). In this case, the so-called tenter method can be used. In addition, the above-mentioned stretching can be dry stretching in the atmosphere, or wet stretching in a state where the PVA film or the resin layer is swollen using a solvent. In order to show the performance of the linear polarization layer, the stretching ratio is 4 times or more, preferably 5 times or more, and particularly preferably 5.5 times or more. The upper limit of the stretching ratio is not particularly limited, but from the perspective of suppressing breakage, it is preferably 8 times or less.

[0153] The linear polarizing layer produced by the production method using the base film can be obtained by laminating the protective layer and then peeling off the base film. According to this method, the linear polarizing layer can be further thinned.

[0154] The thickness of the linear polarizing layer of the PVA film is preferably 1 μm or more, 2 μm or more, or 5 μm or more, and is preferably 30 μm or less, more preferably 15 μm or less, 10 μm or less, or 8 μm or less.

[0155] The film containing a liquid crystal linear polarizing layer can include a linear polarizing layer obtained by coating a composition containing a pigment having liquid crystal and absorption anisotropy, or a composition containing a pigment having absorption anisotropy and a polymerizable liquid crystal on a substrate film. The liquid crystal linear polarizing layer can be a cured product of a polymerizable liquid crystal compound, or it can include an orientation layer. As an orientation layer, an orientation layer included in the phase difference layer described later can be cited. The film containing a liquid crystal linear polarizing layer can be a liquid crystal linear polarizing layer, or it can have a laminated structure of a liquid crystal linear polarizing layer and a substrate film. As a substrate film, for example, a film using a resin material described as a thermoplastic resin for forming a protective film as a protective layer described later can be cited. As a film containing a liquid crystal linear polarizing layer, for example, a polarizing layer described in Japanese Patent Gazette No. 2013-33249 can be cited.

[0156] The total thickness of the substrate film and the linear polarizing layer formed as described above is preferably small. However, if it is too small, the strength decreases and the processability tends to be poor. Therefore, it is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.

[0157] (Protective layer)

[0158] As the protective layer, for example, there can be mentioned a protective film which is a film formed of a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, water barrier, isotropy, stretchability, etc.; an overcoat layer formed of a composition having excellent solvent resistance, transparency, mechanical strength, thermal stability, shielding property, isotropy, etc. The protective film is preferably laminated on the linear polarizing layer via a laminating layer, and the overcoat layer is preferably laminated in direct contact with the linear polarizing layer.

[0159] Specific examples of thermoplastic resins for forming the protective film include cellulose resins such as triacetyl cellulose; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having a ring system and a norbornene structure (also referred to as norbornene resins); (meth) acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins and mixtures thereof. The thickness of the protective film is preferably 3 μm or more, more preferably 5 μm or more, and preferably 50 μm or less, more preferably 30 μm or less.

[0160] The outer coating layer can be formed of a composition having excellent solvent properties, transparency, mechanical strength, thermal stability, shielding properties, and isotropy. The outer coating layer can be formed, for example, by coating the above composition on the linear polarizing layer. As materials constituting the outer coating layer, for example, photocurable resins, water-soluble polymers, etc. can be cited, and (meth) acrylic resins, polyvinyl alcohol resins, polyamide epoxy resins, etc. can be used. The thickness of the outer coating layer can be, for example, 0.1 μm or more and 10 μm or less.

[0161] The protective layer may have anti-reflection properties, anti-glare properties, hard coating properties, etc. (hereinafter, a protective film having such properties is sometimes referred to as a "functional protective layer".). In the case where the protective layer is not a functional protective layer, a surface functional layer such as an anti-reflection layer, an anti-glare layer, a hard coating layer, etc. may be provided on one side of the linear polarizing plate. The surface functional layer is preferably provided in direct contact with the protective layer. The surface functional layer is preferably provided on the side of the protective layer opposite to the linear polarizing layer side.

[0162] Although the case where the protective layer is provided on the linear polarization layer has been described above, the protective layer may be provided on the phase difference layer.

[0163] (Phase difference layer)

[0164] The phase difference layer may be a stretched film or a film including a cured layer of a polymerizable liquid crystal compound.

[0165] When the phase difference layer is a stretched film, the stretched film may be a conventionally known stretched film, and a stretched film imparted with a phase difference by uniaxially stretching or biaxially stretching a resin film may be used. As the resin film, cellulose films such as triacetyl cellulose and diacetyl cellulose, polyester films such as polyethylene terephthalate, polyethylene isophthalate, and polybutylene terephthalate, acrylic resin films such as polymethyl (meth)acrylate and polyethyl (meth)acrylate, polycarbonate films, polyether sulfone films, polysulfone films, polyimide films, polyolefin films, polynorbornene films, etc. may be used, but are not limited thereto.

[0166] When the phase difference layer includes the cured product layer, a known polymerizable liquid crystal compound can be used as the polymerizable liquid crystal compound. The polymerizable liquid crystal compound is a compound having at least one polymerizable group and having liquid crystallinity.

[0167] The so-called polymerizable group possessed by the polymerizable liquid crystal compound means a group participating in the polymerization reaction, preferably a photopolymerizable group. The so-called photopolymerizable group refers to a group that can participate in the polymerization reaction through active free radicals, acids, etc. generated by a photopolymerization initiator. As a polymerizable group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (meth) acryloyloxy, oxirane, oxetane, styryl, allyl, etc. can be cited. Among them, (meth) acryloyloxy, vinyloxy, oxirane and oxetane are preferred, and acryloyloxy is more preferred. The liquid crystal of the polymerizable liquid crystal compound can be a thermotropic liquid crystal or a lyotropic liquid crystal. If the thermotropic liquid crystal is classified by order, it can be a nematic liquid crystal or a smectic liquid crystal. In the case of using two or more polymerizable liquid crystal compounds in combination to form a cured layer of a polymerizable liquid crystal compound, it is preferred that at least one has two or more polymerizable groups in the molecule.

[0168] In the case where the phase difference layer includes the above-mentioned cured product layer, the phase difference layer may include an orientation layer. The orientation layer has an orientation restriction force that orients the polymerizable liquid crystal compound in a desired direction. The orientation layer may be a vertical orientation layer that orients the molecular axis of the polymerizable liquid crystal compound vertically relative to the plane direction of the laminate, or a horizontal orientation layer that orients the molecular axis of the polymerizable liquid crystal compound horizontally relative to the plane direction of the laminate, or an inclined orientation layer that orients the molecular axis of the polymerizable liquid crystal compound obliquely relative to the plane direction of the laminate.

[0169] Regarding the above-mentioned solidified material layer, a composition for forming a phase difference layer containing a polymerizable liquid crystal compound and a solvent, and various additives used as needed is applied to the orientation layer to form a coating film, and the coating film is solidified (hardened), thereby forming a solidified material layer of the polymerizable liquid crystal compound. Alternatively, the above-mentioned composition can be applied to a substrate film to form a coating film, and the coating film is stretched together with the substrate film to form a solidified material layer. The above-mentioned composition may further include a polymerization initiator, a reactive additive, a leveling agent, an inhibitor, etc. in addition to the above-mentioned polymerizable liquid crystal compound and the solvent. Polymerizable liquid crystal compounds, solvents, polymerization initiators, reactive additives, leveling agents, inhibitors, etc. can appropriately use known substances. As a substrate film, a film of a resin material described as a thermoplastic resin for forming a protective film as a protective layer can be used.

[0170] (Surface protection film)

[0171] The surface protection film is provided so as to be releasable relative to the polarizing plate. The surface protection film may have a single-layer structure or a multi-layer structure. The surface protection film may include a substrate layer and a second adhesive layer, or may be a self-adhesive substrate layer.

[0172] As the substrate layer constituting the surface protection film, a film of the resin material described above as a thermoplastic resin for forming a protective film as a protective layer can be used. As the adhesive composition for forming the second adhesive layer, a known adhesive composition can be used to form it. As a known adhesive composition, the composition described in the above-mentioned adhesive composition can be cited.

[0173] The surface protective film comprising the substrate layer and the second adhesive layer can be formed by applying the adhesive composition itself or an organic solvent dilution of the adhesive composition on the substrate layer and drying. As a method for applying the adhesive composition or its organic solvent dilution, for example, a bar coating method, a knife coating method, a roller coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be cited.

[0174] When the surface protection film has self-adhesiveness, examples of the thermoplastic resin constituting the self-adhesive base layer include polypropylene-based resins and polyethylene-based resins.

[0175] In the above, the case where the surface protection film is used for the polarizing plate is described. However, the surface protection film may be laminated on a member exemplified as an optical film other than the polarizing plate.

[0176] (Lamination layer)

[0177] When the optical film has a multilayer structure, the interlayers can be laminated using a laminating layer. The laminating layer is an adhesive layer or an adhesive layer. When the laminating layer is an adhesive layer, it can be formed using a known adhesive composition. As a known adhesive composition, the composition described in the above-mentioned adhesive composition can be cited.

[0178] When the laminating layer is an adhesive layer, the adhesive layer can be formed by curing the curable component in the adhesive composition. The adhesive composition used to form the adhesive layer is an adhesive other than a pressure-sensitive adhesive (adhesive), for example, a water-based adhesive, an active energy ray-curable adhesive.

[0179] Examples of the water-based adhesive include those obtained by dissolving or dispersing a polyvinyl alcohol resin in water. The drying method when using the water-based adhesive is not particularly limited, and for example, a method of drying using a hot air dryer or an infrared dryer may be used.

[0180] Examples of active energy ray-curable adhesives include solvent-free active energy ray-curable adhesives containing curable compounds that are cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays. By using solvent-free active energy ray-curable adhesives, interlayer adhesion can be improved.

[0181] Example

[0182] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. "%" and "part" in Examples and Comparative Examples are mass % and mass parts unless otherwise specified.

[0183] [Preparation of release film (1)]

[0184] (Preparation of Stripping Agent Composition a)

[0185] 1 part of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex (trade name: "SRX212" purchased from DOW TORAY Co., Ltd.) was mixed as a catalyst with 100 parts of a toluene solution of a silicone resin (manufactured by DOW TORAY Co., Ltd., trade name: "LTC759" (solid content concentration 30%)). A mixed solvent of toluene and methyl ethyl ketone (mass ratio of 1:1) was mixed into the obtained mixture to prepare a solid content concentration of 1.5%, thereby obtaining a stripping agent composition a.

[0186] (Preparation of Release Film (1))

[0187] A transparent polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation, trade name: DIAFOILT190E38, thickness 38 μm) was prepared. Then, the release agent composition a obtained above was applied to one surface of the PET film using a bar coater so that the thickness after drying was 100 nm, and dried at a temperature of 120° C. for 3 minutes to form a release treatment layer on the PET film. The film formed with the release treatment layer was stored for more than 5 days under an environment of a temperature of 23° C. and a relative humidity of 55%, thereby obtaining a release film (1) having a release treatment layer formed on the PET film.

[0188] [Preparation of release film (2)]

[0189] (Preparation of Stripping Agent Composition b)

[0190] 1 part of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex (trade name: "SRX212" purchased from DOW TORAY Co., Ltd.) was mixed as a catalyst with 100 parts of a toluene solution of a silicone resin (manufactured by DOW TORAY Co., Ltd., trade name: "LTC759" (solid content concentration 30%)). Then, 10 parts of a xylene and ethylbenzene solution of a vinyl-modified silicone resin (manufactured by DOW TORAY Co., Ltd., trade name: "SD7292" (solid content concentration 65%, containing 3% by mass of vinyl in the solid content) were further added. A mixed solvent of toluene and methyl ethyl ketone (mass ratio of 1:1) was mixed with the obtained mixture to prepare a solid content concentration of 1.5%, thereby obtaining a stripping agent composition b.

[0191] (Preparation of Release Film (2))

[0192] A release film (2) was obtained in the same manner as in the preparation of the release film (1) except that the release agent composition b was used instead of the release agent composition a.

[0193] [Preparation of release film (3)]

[0194] (Preparation of Stripping Agent Composition c)

[0195] 1 part of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex (trade name: "SRX212" purchased from DOW TORAY Co., Ltd.) was mixed as a catalyst with 100 parts of a toluene solution of a silicone resin (manufactured by DOW TORAY Co., Ltd., trade name: "LTC759" (solid content concentration 30%)). Then, 5 parts of a xylene and ethylbenzene solution of a vinyl-modified silicone resin (manufactured by DOW TORAY Co., Ltd., trade name: "SD7292" (solid content concentration 65%, containing 3% by mass of vinyl in the solid content) were further added. A mixed solvent of toluene and methyl ethyl ketone (mass ratio of 1:1) was mixed with the obtained mixture to prepare a solid content concentration of 1.5%, thereby obtaining a stripping agent composition c.

[0196] (Preparation of Release Film (3))

[0197] A release film (3) was obtained in the same manner as in the preparation of the release film (1) except that the release agent composition c was used instead of the release agent composition a.

[0198] [Preparation of Adhesive Compositions (1) to (3)]

[0199] (Preparation of acrylic resin solution (1))

[0200] A mixed solution of 45 parts of ethyl acetate, 34 parts of butyl acrylate, 10 parts of methyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate and 0.5 parts of acrylic acid was added to a reaction container equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirrer, and the internal temperature was raised to 55°C while replacing the air in the device with nitrogen to make it oxygen-free. Thereafter, the entire amount of a solution prepared by dissolving 0.14 parts of azobisisobutyronitrile in 9.86 parts of ethyl acetate as a polymerization initiator was added. After the addition of the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction container at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54 to 56°C. The addition of ethyl acetate was stopped when the concentration of the acrylic resin reached 35%, and the temperature was further maintained until 12 hours had passed since the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the acrylic resin to 20%, thereby preparing an acrylic resin solution (1). The weight average molecular weight Mw of the obtained acrylic resin was 1.3 million, and the molecular weight distribution Mw / Mn was 4.2. Mw and Mn were measured by configuring two "TSKgel GMHHR-H (S)" manufactured by TOSOH Corporation in series as chromatographic columns in a GPC apparatus, using tetrahydrofuran as an eluent, and measuring by standard polystyrene conversion under the conditions of a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40°C, and a flow rate of 1 mL / min.

[0201] (Preparation of Adhesive Composition (1))

[0202] To 100 parts of the solid content of the acrylic resin solution (1) obtained above, 0.5 parts of a crosslinking agent (trade name "CORONATE L" manufactured by TOSOH Corporation (ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid content concentration 75 mass %)) was added on an effective ingredient basis, and ethyl acetate was further added to adjust the solid content concentration to 16%, thereby obtaining an adhesive composition (1).

[0203] (Preparation of Adhesive Composition (2))

[0204] To 100 parts of the solid content of the acrylic resin solution (1) obtained above, 0.5 parts of a crosslinking agent (Mitsui Chemicals: trade name "D-103" (ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid content concentration 75 mass %)) was added on an effective ingredient basis, and 0.1 parts of a silane compound (Shin-Etsu Chemical Co., Ltd.: trade name "KBM-403" (3-glycidoxypropyltrimethoxysilane) was added on an effective ingredient basis, and ethyl acetate was further added to adjust the solid content concentration to 16%, thereby obtaining an adhesive composition (2).

[0205] (Preparation of Adhesive Composition (3))

[0206] To 100 parts of the solid content of the acrylic resin solution (1) obtained above, 0.5 parts of a crosslinking agent (Mitsui Chemicals: trade name "D-103" (ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid content concentration 75 mass %)) was added on an effective ingredient basis, and 0.1 parts of a silane compound (Shin-Etsu Chemical Co., Ltd.: trade name "KR-519" (mercapto group-containing silicone oligomer) was added on an effective ingredient basis, and ethyl acetate was further added to adjust the solid content concentration to 16%, thereby obtaining an adhesive composition (3).

[0207] [Preparation of adhesive sheet (1)]

[0208] The adhesive composition (1) obtained above was applied to the release-treated layer (release-treated surface) of the release film (2) obtained above using a coater, and then dried at a temperature of 100° C. for 1 minute to obtain an adhesive layer (1) having a thickness of 20 μm. The release-treated layer (release-treated surface) of the release film (1) obtained above was laminated on the side of the obtained adhesive layer (1) opposite to the release film (2) side. The obtained laminate was allowed to stand for 7 days or more under an environment of a temperature of 23° C. and a relative humidity of 60%, to obtain an adhesive sheet (1).

[0209] [Preparation of adhesive sheet (2)]

[0210] The adhesive composition (2) obtained above was applied to the release treatment layer (release treatment surface) of the release film (2) obtained above using a coater, and then dried at a temperature of 100° C. for 1 minute to obtain an adhesive layer (2) having a thickness of 20 μm. The release treatment layer (release treatment surface) side of the release film (1) obtained above was laminated on the side of the obtained adhesive layer (2) opposite to the release film (2) side. The obtained laminate was left to stand for 7 days or more under an environment of a temperature of 23° C. and a relative humidity of 60%, to obtain an adhesive sheet (2).

[0211] [Preparation of adhesive sheet (3)]

[0212] The adhesive composition (3) obtained above was applied to the release treatment layer (release treatment surface) of the release film (2) obtained above using a coater, and then dried at a temperature of 100° C. for 1 minute to obtain an adhesive layer (3) having a thickness of 20 μm. The release treatment layer (release treatment surface) of the release film (1) obtained above was laminated on the side of the obtained adhesive layer (3) opposite to the release film (2) side. The obtained laminate was left to stand for 7 days or more under an environment of a temperature of 23° C. and a relative humidity of 60%, to obtain an adhesive sheet (3).

[0213] [Preparation of adhesive sheet (4)]

[0214] The adhesive composition (3) obtained above was applied to the release treatment layer (release treatment surface) of the release film (3) obtained above using a coater, and then dried at a temperature of 100° C. for 1 minute to obtain an adhesive layer (4) having a thickness of 20 μm. The release treatment layer (release treatment surface) side of the release film (1) obtained above was laminated on the side of the obtained adhesive layer (4) opposite to the release film (3) side. The obtained laminate was allowed to stand for 7 days or more under an environment of a temperature of 23° C. and a relative humidity of 60%, to obtain an adhesive sheet (4).

[0215] (Evaluation of peelability of pressure-sensitive adhesive sheet)

[0216] Under the conditions of a temperature of 23°C and a relative humidity of 60%, the release film (1) having a relatively smaller release force than the release film (2) or (3) was peeled off by hand from the adhesive sheets (1) to (4) obtained above. As a result, the release film (1) could be peeled off without tearing the adhesive layer. In addition, the surface of the release treatment layer side of the peeled release film (1) was observed and evaluated according to the following criteria. The results are shown in Table 1.

[0217] a: No transfer (residue) of the adhesive layer is observed on the release-treated surface, or only a trace amount is observed.

[0218] b: Transfer of the adhesive layer (adhesive residue) was observed on the release-treated surface.

[0219] [Comparative Example 1]

[0220] (Production of polarizing plate)

[0221] A polarizing plate was obtained by laminating a first protective film (triacetyl cellulose film) with a thickness of 25 μm on one side of a linear polarizing layer (a polarizing film in which iodine was adsorbed and oriented on a uniaxially stretched polyvinyl alcohol film) through an adhesive, and laminating a second protective film (triacetyl cellulose film) with a thickness of 20 μm on the other side through an adhesive. Then, a surface protective film was laminated on the side of the first protective film to obtain a polarizing plate with a surface protective film. The surface protective film had a structure in which a 15 μm adhesive layer was laminated on a 38 μm thick PET film. The thickness of the polarizing plate with a surface protective film was 110 μm.

[0222] (Production of optical layered body (c1))

[0223] The surface of the polarizing plate with a surface protective film obtained above on the second protective film side is subjected to corona treatment, and the adhesive layer (1) exposed by peeling off the release film (1) of the adhesive sheet (1) obtained above is bonded to the corona treated surface to obtain an optical laminate (c1). The layer structure of the optical laminate (c1) is polarizing plate with a surface protective film (surface protective film / first protective film / linear polarization layer / second protective film) / adhesive layer (1) / release film (2).

[0224] [Comparative Example 2]

[0225] An optical laminate (c2) was obtained by the same method as in Comparative Example 1 except that the adhesive sheet (2) was used instead of the adhesive sheet (1). The layer structure of the optical laminate (c2) was a polarizing plate with a surface protective film (surface protective film / first protective film / linear polarizing layer / second protective film) / adhesive layer (2) / release film (2).

[0226] [Comparative Example 3]

[0227] An optical laminate (c3) was obtained by the same method as in Comparative Example 1 except that the adhesive sheet (3) was used instead of the adhesive sheet (1). The layer structure of the optical laminate (c3) was a polarizing plate with a surface protective film (surface protective film / first protective film / linear polarizing layer / second protective film) / adhesive layer (3) / release film (2).

[0228] [Comparative Example 4]

[0229] An optical layered body (c4) was obtained by the same method as in Comparative Example 1 except that the pressure-sensitive adhesive sheet (4) was used instead of the pressure-sensitive adhesive sheet (1). The layer structure of the optical layered body (c4) was a polarizing plate with a surface protection film (surface protection film / first protection film / linear polarization layer / second protection film) / pressure-sensitive adhesive layer (4) / release film (3).

[0230] [Example 1]

[0231] (Production of optical layered body (1))

[0232] An optical laminate (c1) was obtained by the steps described in Comparative Example 1. The release film (2) was peeled off from the optical laminate (c1), and the release-treated layer side of the release film (1) obtained above was laminated on the exposed adhesive layer (1) to obtain an optical laminate (1). The layer structure of the optical laminate (1) was a polarizing plate with a surface protective film (surface protective film / first protective film / linear polarizing layer / second protective film) / adhesive layer (1) / release film (1).

[0233] [Example 2]

[0234] (Production of optical laminate (2))

[0235] An optical laminate (c2) was obtained by the procedure described in Comparative Example 2. The release film (2) was peeled off from the optical laminate (c2), and the release-treated layer side of the release film (1) obtained above was laminated on the exposed adhesive layer (2) to obtain an optical laminate (2). The layer structure of the optical laminate (2) was a polarizing plate with a surface protective film (surface protective film / first protective film / linear polarizing layer / second protective film) / adhesive layer (2) / release film (1).

[0236] [Example 3]

[0237] (Production of optical laminate (3))

[0238] An optical laminate (c3) was obtained by the procedure described in Comparative Example 3. The release film (2) was peeled off from the optical laminate (c3), and the release-treated layer side of the release film (1) obtained above was laminated on the exposed adhesive layer (3) to obtain an optical laminate (3). The layer structure of the optical laminate (3) was a polarizing plate with a surface protective film (surface protective film / first protective film / linear polarizing layer / second protective film) / adhesive layer (3) / release film (1).

[0239] [Example 4]

[0240] (Production of optical layered body (4))

[0241] An optical laminate (c4) was obtained by the procedure described in Comparative Example 4. The release film (3) was peeled off from the optical laminate (c4), and the release-treated layer side of the release film (1) obtained above was laminated on the exposed adhesive layer (4) to obtain an optical laminate (4). The layer structure of the optical laminate (4) was a polarizing plate with a surface protective film (surface protective film / first protective film / linear polarizing layer / second protective film) / adhesive layer (4) / release film (1).

[0242] [XPS measurement]

[0243] The release film was peeled off from the optical laminate obtained in the examples and comparative examples, and the surface of the release-treated layer side of the peeled release film (release-treated surface) and the surface of the release film side of the exposed adhesive layer were subjected to XPS measurement under the following conditions using an XPS apparatus (K-Alpha+, manufactured by Thermofisher Scientific). The sample size was set to 10 mm×10 mm.

[0244] (XPS measurement conditions)

[0245] X-ray irradiation: monochromated Al Kα (12kV / 6mA), 400μm

[0246] Dwell time: 50ms

[0247] Pass energy: 50eV

[0248] Target orbitals: C1s, O1s, Si2p

[0249] In the XPS spectrum (Sr) of the peeling treatment surface obtained by XPS measurement and the XPS spectrum (Sa) of the surface on the peeling film side of the adhesive layer, the intensity Xs of the maximum peak Ps and the intensity Xa of the maximum peak Pa in the range of binding energy of 96 eV or more and 108 eV or less are determined. In addition, in each XPS spectrum (Sr) and (Sa), the intensity Ys of the XPS spectrum (Sr) at a position 2 eV on the high energy side (binding energy (Es+2)) relative to the binding energy Es at the peak Ps, and the intensity Ya of the XPS spectrum (Sa) at a position 2 eV on the high energy side (binding energy (Ea+2)) relative to the binding energy Ea at the peak Pa are determined. Based on the determined intensities, the value of the left side (Ys / Xs×100) of the above formula (1) and the value of the left side (Ya / Xa×100) of the above formula (2) are determined. The results are shown in Tables 1 and 2.

[0250] It should be noted that in Examples 1 to 4, the values ​​(Ys2 / Xs2×100) obtained by multiplying the left side of the above formula (3) by 100 for the release-treated surface of the release film (2) or (3) released from the optical layered bodies (c1) to (c4) can be regarded as the values ​​of the left side (Ys / Xs×100) of the above formula (1) determined in Comparative Examples 1 to 4. The values ​​(Ys1 / Xs1×100) obtained by multiplying the right side of the above formula (3) by 100 for the release-treated surface of the release film (1) released from the optical layered bodies (1) to (4) in Examples 1 to 4 and the values ​​of the left side (Ys1 / Xs1×100) of the above formula (4) can be regarded as the values ​​of the left side (Ys / Xs×100) of the above formula (1) determined in Examples 1 to 4. In Examples 1 to 4, the value (Ya2 / Xa2×100) obtained by multiplying the left side of the above-mentioned formula (5) by 100 can be regarded as the value (Ya / Xa×100) of the left side of the above-mentioned formula (2) determined in Comparative Examples 1 to 4. In Examples 1 to 4, the value (Ya1 / Xa1×100) obtained by multiplying the right side of the above-mentioned formula (5) by 100 and the value (Ya1 / Xa1×100) of the left side of the above-mentioned formula (6) can be regarded as the value (Ya / Xa×100) of the left side of the above-mentioned formula (2) determined in Examples 1 to 4.

[0251] [Peel force measurement of release film]

[0252] The optical laminate obtained in the examples and comparative examples was cut into a size of 50 mm in width and 190 mm in length to obtain a test sample. A universal testing machine (AGS-X 50N, manufactured by Shimadzu Corporation) was used to clamp the release film of the test sample and measure the peeling force when peeled in a 180° direction at a speed of 300 mm / min. The results are shown in Tables 1 and 2.

[0253] [Releasability Test of Release Film of Optical Laminated Body]

[0254] The optical layered bodies obtained in Examples and Comparative Examples were cut into a size of 50 mm in width×50 mm in length to obtain test samples. Next, the adhesive surface of a double-sided tape (Nicetack General Type (25 mm width) manufactured by NICHIBAN Co., Ltd.) was laminated on the substrate surface of a repair tape (3M, trade name: Scotch Mending Tape (24 mm width)) and cut into a size of 10 mm × 10 mm. The adhesive surface of the repair tape of the laminate of the repair tape and the double-sided tape was attached to the center of the surface protective film side of the test sample, and after peeling off the release paper of the double-sided tape, the adhesive surface of the double-sided tape was attached to the glass plate to fix the test sample on the glass plate. A polyimide tape (Kapton tape) (Nitto Denko, trade name: No. 360UL (13 mm width)) cut into 30 mm × 13 mm was attached to one corner of the release film side surface of the test sample fixed to the glass plate so as to protrude 20 mm from the corner. The state of the polyimide tape attached to the test sample when peeled off by hand was judged according to the following criteria. The results are shown in Tables 1 and 2.

[0255] a: Only the release film is completely released from the optical laminate.

[0256] b: The release film was not completely released from the optical laminate, and the optical laminate was released from the repair tape.

[0257] [Table 1]

[0258]

[0259] [Table 2]

[0260]

[0261] In the optical laminates (1) to (4) obtained in the examples, in which the release film (2) or (3) was replaced with the release film (1), the release force of the release film (1) was reduced, and even in the peelability test, only the release film was completely peeled off, so it is considered that the release film (1) can be well peeled off from the optical laminates (1) to (4). In the optical laminates (c1) to (c4) having the release film (release film (2) or (3)) obtained in the comparative examples, the release force of the release film was still large, and even in the peelability test, the release film was not completely peeled off, so it is considered that it is difficult to peel the release film from the optical laminates (c1) to (c4).

[0262] Description of Reference Numerals

[0263] 1 Optical laminate, 2 First laminate, 3 Second laminate, 11 Optical film, 12 First adhesive layer (adhesive layer), 15 First release film (release film), 20 Adhesive sheet, 21 Adhesive layer with release film, 25 Second release film, 26 Third release film.

Claims

1. An optical laminate comprising an optical film, an adhesive layer and a release film in this order, The release film has a release-treated surface containing a silicone compound on the side in contact with the adhesive layer. The release-treated surface of the release film satisfies the following formula (1): Ys / Xs×100≤3.5 (1) In formula (1), Xs represents the intensity of the largest peak Ps in the range of binding energy of 96 eV or more and 108 eV or less in the XPS spectrum Sr of the peeling-treated surface, Ys represents the intensity of Sr in the XPS spectrum at a binding energy of (Es+2) eV when the binding energy at the peak Ps is Es [eV].

2. The optical layered body according to claim 1, wherein: The surface of the adhesive layer on the release film side satisfies the following relationship (2): Ya / Xa×100≥2.0 (2) In formula (2), Xa represents the intensity of the maximum peak Pa in the range of binding energy of 96 eV or more and 108 eV or less in the XPS spectrum Sa of the surface of the adhesive layer on the release film side, Ya represents the intensity of the XPS spectrum Sa at a binding energy of (Ea+2) eV when the binding energy at the peak Pa is set to Ea [eV].

3. The optical layered body according to claim 1, wherein: The optical film has a thickness of 120 μm or less.

4. The optical layered body according to any one of claims 1 to 3, wherein The optical film is a polarizing plate including at least a linear polarizing layer.

5. The optical layered body according to claim 4, wherein: The polarizing plate further includes a phase difference layer.

6. The optical layered body according to claim 4, wherein: The optical film includes a surface protection film provided in a releasable manner with respect to the polarizing plate.

Citation Information

Patent Citations

  • Polarization element, circularly polarizing plate and method of manufacturing those

    JP2013033249A

  • Tacky-adhesive sheet for optical use, and method for producing the sheet

    JP2015052073A